Treatment of combined endodontic: periodontic lesion by sealing of palato-radicular groove using biodentine - Naik, Mayuri (J Conserv Dent, 2014)
INTRODUCTION: Palatoradicular groove is a developmental anomaly which is predominantly found in maxillary lateral incisors. It provides a susceptible alcove for the progression of localised periodontal inflammation which can further cause pulpal involvement. This case report describes the successful treatment of a large periodontic – endodontic lesion usingnon surgical endodontic therapy and biodentine for the sealing of the palatoradicular groove.